Persuasion as a Communication Tool - Laura Gorham; Ricky Telg; Tracy Irani (EDIS)
Think about a time when you wanted your parents to do something for you, such as buy you a special birthday gift, let you stay up late, or go out with your friends. Your attempts at persuasion probably focused on communicating specific reasons why your parents should take the action you wanted. Persuasion is a communication tool that can be adjusted to convince a single person, or to move an entire audience to a desired action. In this publication you will learn several techniques for persuasive communication. This 2-page fact sheet was written by Laura Gorham, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, July 2013.